Perlindungan Hukum terhadap Nasabah dalam Penundaan Kredit Terdampak Covid 19 - Sang Nyoman Angga Diputra; Ni Luh Made Mahendrawati; Ni Made Puspasutari Ujianti (Jurnal Konstruksi Hukum, 2021)
Humans as social beings who live side by side and have various needs that must be met in order to survive. In meeting these needs. Indonesia often makes payments with a credit system. Credit is a breakthrough that really helps the community. However, with the Covid-19 Pandemic) hitting various businesses and credit financing customers due to lack of income. This study aims to examine the legal arrangements for credit delays for customers affected by COVID-19 in Indonesia and explain legal protection for customers affected by COVID-19 in Indonesia. The type of research applied in this research is normative legal research, with a statutory approach and a concept approach. In general, the regulation of credit delays for customers affected by COVID-19 is regulated in POJ K Number II POJK.03 2020 regarding the national economic stimulus as a counter-helical policy for the impact of the 2019 coronavirus disease. There are two legal protections, namely preventive legal protection by issuing PERPU Number I of 2020 concerning state financial policies and stability for handling the coronavirus disease 19 pandemic, and repressive legal protection based on Bank Indonesia Circular Letter No. 26/4/BPPP which in principle regulates the rescue of non-performing loans through rescheduling, reconditioning, restructuring